2017
DOI: 10.1016/j.trecan.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer: Multiple Subtypes within a Tumor?

Abstract: Breast cancer is a heterogeneous disease and stratification of tumors is paramount to achieve better clinical outcomes. While it is common to stratify and treat breast tumors as a single entity, insights from studies on intra-tumoral heterogeneity and cancer stem cells raise the possibility that multiple breast cancer subtypes may co-exist within a tumor. A role for plasticity in driving dynamic conversions between breast cancer subtypes is proposed and the clinical implications would be a need for combinatori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
213
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 310 publications
(242 citation statements)
references
References 69 publications
3
213
1
4
Order By: Relevance
“…Changes in the compositions of lipid isomers are indicators of altered stearoyl-CoA desaturase (SCD) or phospholipase activities 59 . Existing studies have shown that cancer cells in solid tumors are heterogeneous, which could lead to large variations in lipid compositions of tissues from different patients 64 . Among the total 43 PC structure isomers identified, 29 were sn-isomers and 14 were C=C location isomers.…”
Section: Analysis Of Paired Normal and Cancerous Human Lung Tissuesmentioning
confidence: 99%
“…Changes in the compositions of lipid isomers are indicators of altered stearoyl-CoA desaturase (SCD) or phospholipase activities 59 . Existing studies have shown that cancer cells in solid tumors are heterogeneous, which could lead to large variations in lipid compositions of tissues from different patients 64 . Among the total 43 PC structure isomers identified, 29 were sn-isomers and 14 were C=C location isomers.…”
Section: Analysis Of Paired Normal and Cancerous Human Lung Tissuesmentioning
confidence: 99%
“…Breast cancer is the second major cause of death in women, and its heterogeneous molecular nature is a significant obstacle in treatment planning [65]. It has several subtypes, such as human epidermal growth factor receptor 2 (HER2), triple-negative or basal-like, Luminal A and Luminal B type depending on the presence or absence of several hormone receptors like HER2, estrogen, and progesterone [66][67][68]. Recently, another subtype of breast cancer known as the claudin-low subtype has been reported [67].…”
Section: Claudin-1 and Breast Cancermentioning
confidence: 99%
“…It is therefore needed to elicit a better response with treatment strategies in patients. 2 According to the profiling of gene expression, breast cancer has been classified into four types: luminal A, luminal B, basal-like breast cancer and HER-2 overexpressed breast cancer. Luminal A being the most common type consists of ER and/or PR positive, HER-2 negative and Ki-67 expression less than 14%.…”
Section: Introductionmentioning
confidence: 99%